Foreword (to Sumer XIX/1-2) - el-Wailly, Faisal
1. Departmental Excavations: Tell as-Sawwan; 2. Foreign Excavations; 3. Preservation of monuments: A. Qara Serai; B. The Mausoleum of Imam ‛Awn ud-Din; C. Hatra; D. Ana; E. Samarra; F. Khan Dari; G. The Arch of Ctesiphon; H. Ur; I. Babylon; ersch. 1965.